Sociality and signaling activity modulate information flow in river otter communication networks. (10th November 2020) - Barocas, Adi; Golden, Howard N; Dudenhoeffer, Megan; Ben-David, Merav
Abstract: Animal communication networks are built from interactions between senders and receivers of signals. The drivers of signaling decisions, which are the building blocks of such networks, are not well understood. Theory predicts that conditions which ensure information spread to the largest possible number of receivers should be favored. Several carnivores use latrine sites for visual, olfactory, and auditory signaling. We tested the hypotheses that signaling behavior at latrine sites is influenced by social structure and locally acquired information on the presence of conspecifics, using coastal river otters ( Lontra canadensis ), in Alaska. River otters exhibit a flexible social system of mostly males that communicate through scent marking at latrines. During scent marking, river otters also perform feet stomping, which may add a visual component to their signal. Using trail camera footage, we found that solitary otters were more likely to perform both sniffing and scent marking compared with otters in groups. Feet stomping was more intense for solitary otters but less pronounced during overmarking. Signalers demonstrated a greater tendency to scent mark when in smaller groups at highly active latrines, whereas feet stomping was more intense in recently visited sites. When in groups, scent-marking frequency increased when other individuals were signaling, suggesting a positive feedback, possibly driven by feet stomping. In concert, our results suggest that in river otters, scent-marking decisions minimize signal dilution by being performed in small groups and maximize the receivers through preferential signaling at latrines with higher, more recent activity. Because signaling decisions in social animals are linked to key life-history events such as mating and group membership shifts, understanding their individual and population-level drivers can be crucial. Abstract : When animals use signals to communicate, the conditions under which information flow is optimal are not well understood. We studied scent-marking behavior in social river otters visiting latrines. We found higher tendency to scent mark in smaller groups, in more active locations and when other individuals were signaling. Our results indicate that signaling decisions are driven by reducing the dilution of the information sent and reaching the most receivers.